Comparative Studies on the Amylase and Cellulase Production of Aspergillus and Penicillium - Ibatsam Khokhar; Irum Mukhtar; Sobia Mushtaq (Journal of Applied Sciences and Environmental Management)
Filamentous fungi are important due to their high enzymes production potential. Many enzymes produced by fungi have related to biotechnological applications in several industrial sectors. The purpose of this study was to collect and isolate Penicillium and Aspergillus species from different sources and examined for their ability to produce cellulase and amylase. Ten fungal isolates of genera, Aspergilus and Penicillium were examined for their ability to produce industrial important enzymes. All fungal isolates exhibited high DCZ/DFC ratio in cellulase and amylayes activity. It was also evident that starch and cellulose medium effected the fungal growth. Four Penicillium species viz. P. janthinellum (IK-48), P. melinii (IK-49) and P. velutinum (IK- 51) and P. waskmanii (IK- 50) showed the increased growth in starch and cellulose medium as compare to control. P. waskmanii (IK- 50) showed the highest growth stimulation in the cellulose and starch medium. This study contributes to catalogue local fungal isolated in Pakistan, and provides additional information to support future research about the industrial potential of these microorganisms for enzymes and, eventually, also secondary metabolites with anti-microbial or anti-parasitic activities. @JASEM